DEVELOPING DYNAMICS OF THE MONARQUÍA ESPAÑOLA CONCEPT IN THE 16TH -20TH CENTURIES - Popova , Natalia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article gives a complex synchronic-diachronic analysis of the Spanish nationally-marked concept MONARQUÍA ESPAÑOLA, which occupies an important place in the national conceptual sphere and is closely linked to many Spanish society’s fields. The conceptual, axiological and associative components of the concept were constantly modified during the 16th-20th centuries, predetermining the evolution of its prototype core. The change of nuclear categories in different historical epochs and the migration of nuclear and peripheral concept elements determined the vectors of its development, including changes in monarchy nature, monarchy’s tendency to adapt to the needs of society and its symbolism in the Spanish people’s minds. The associative concept links actively provoked changes in the set of prototype nuclear categories, determining modifications in the perception and linguistic reflection of the concept. The Spanish language world view reflects the development of the concept MONARQUÍA ESPAÑOLA by a large number of lexical units verbalizing the concept, by metonymic and metaphorical transitions gradually expanding their meaning, by idioms accumulating the national-axiological content of the concept and containing a significant number of potential updates, as well as by microtexts in which the important for each epoch conceptual features were updated. The most significant of them are ABSOLUTA, CATÓLICA, RESPETADA (16th-17th centuries), REFORMISTA (18th century), LIBERAL (19th century), PARLAMENTARIA, REPRESENTATIVA, DEMOCRÁTICA (20th century). The dynamics of the historical development of the concept indicates a permanent increasing of the flexibility of nuclear categories, which correlates with Spanish society’s political, moral and ethical principles. __________ References • Popova N. M. Transformacіja ocіnnostі nacіonal’no-markovanogo konceptu “fe” u movnіj kartinі svіtu Іspanії [Transformation of the nationally-marked concept "fe" value in the Spanish language world view]. Problemi semantiki slova, rechennja ta tekstu [Problems of word semantics, sentence and text], 2013, no. 30, pp. 432–439 (In Ukr.) • Skrobot A. І. Nacіonal’no-kul’turna specifіka іspans’kih paremіj z anіmalіstichnim komponentom [National-cultural specificity of Spanish idioms with an animal component]. Problems of word semantics, sentence and text], 2014, no. 33, pp. 186–193 (In Ukr.) • Hohlova V. A. Nacional’no-kul’turnaja semantika toponimicheskoj frazeologii v anglijskom i ukrainskom jazikah [National-cultural semantics of toponymic phraseology in English and Ukrainian languages]. Science and Education a New Dimension, 2014, Philology, no 24, pp. 63–66 (In Russ.) • Geeraerts D. Diachronic prototype semantics. A contribution to Historical Lexicology. Oxford, Clarendon Press, 1997. 207 р. • GeeraertsD. Prospects and problems of prototype theory. Diacronia, 2016, no. 4. Available at: http://www.diacronia.ro (accessed 20.12.2017) • Ruiz de MendozaF. Cognitive and pragmatic aspects of metonymy. Metaphor and Metonymy at the Crossroads. Berlin–New York, Walter de Gruyter, 2003. Pp. 161–178. • ColmeiroM. Introducción a las cortes de los antiguos reinos de León y Castilla [Introduction to the courts of the ancient kingdoms of León and Castilla] (1884). Alicante, Universidad de Alicante, 2003. 959 p. (In Spanish) • Corpus diacrónico del español (CORDE) [Spanish diachronic corpus]. Madrid, Real Academia Española. Available at: http://www.rae.es. (accessed 8-20.01.2018). (In Spanish) • Diccionario de la lengua española de RAE [Dictionary of the Spanish language of RAE]. Edición tricentinario, 2017. Available at: http://dle.rae.es (accessed 21.01.2018). (In Spanish) • Elliott J. H. España en Europa: Estudios de historia comparada: escritos seleccionados [Spain in Europe: Comparative History Studies: Selected Writings]. Valencia, Universitat de València, 2002. 286 p. (In Spanish) • FeijooB J. Cartas eruditas [Erudite Letters] (1742). Madrid, Alianza Editorial, 1984. 313 p. (In Spanish) • Palafox. Obras Sobre los conceptos [Works. About the concepts] (1762) Valencia, Universitat de València, 1997. 294 p. (In Spanish)